Role Of Physical Therapy In Managing Chronic Lower Back Pain: Evidence-Based Practices (The Review of Diabetic Studies, 2024)
Chronic lower back pain (CLBP) is a pervasive and complex condition necessitating a management shift from passive, pathoanatomical interventions to active, biopsychosocial strategies, with physical therapy serving as a cornerstone of evidence-based care. Contemporary practice integrates pain neuroscience education to reconceptualize pain, cognitive-behavioral principles to address fear-avoidance behaviors, and tailored therapeutic exercise to restore motor control, strength, and function. This holistic approach, which may be augmented by manual therapy as an adjunct and supported by modern paradigms like telerehabilitation, empowers patients through self-management, targeting the multifaceted interplay of physiological, psychological, and social factors that perpetuate chronicity. Ultimately, evidence-based physical therapy provides a sustainable, first-line pathway to reduce disability and improve quality of life by focusing on functional restoration and patient empowerment rather than mere pain elimination.